Prospek Peningkatan Kualitas Ruang Perumahan dan Pemukiman yang Berbasis pada Komunitas Studi Kasus: Lingkungan Permukiman Jalan Gagak - Bandung - Suparti Amir Salim; Syahyudesrina Syahyudesrina; Samsirina Samsirina; Fenita Indrasari (Journal of Visual Art and Design, 2008)
This study looks to understand more on the possibility of improving the quality of housing environment based on community initiative that sustain residents' effort to accommodate changes of their surroundings, by observing housing-environment at jalan Gagak "“ Bandung as an area for case study. The analysis focuses on: (1) the socio-capital of community involvement, stating condition of internal organized efforts in addressing needs of the community, and (2) the roles of external parties, stating the involvement of external actors both of government and privates. For the study, the authors conducted focus-group discussions on group of residents at RW 18 and RW 19 Kelurahan Sadang Serang, Kecamatan Coblong "“ Bandung, as well as interviewing local leaders.Results of observation indicate that residents possess interests and self-trust to develop their environment and willing to provide supplies for it. They have tendency to set preferences on what orderly environment should look like including rejecting ideas of apartment-like housing as it is feared to create "slum"-ness and "inappropriateness" fire-emergency access. As residents put concern on the facts that there are no shared-values among them in addressing problems of space and inactivity of local leaders, resulting in the market-driven changes of spatial development that intervening the needs of public. Thus, it is necessary to decentralize the process of organizing public space, starts from government's unit to community's initiative. This requires strict guidelines that are fair to follow by allowing neutral parties to involve. In addition, there should be internal mechanism to build community's initiative through "musrenbang" as a way to initiate community based development. Having the results, the authors urge future studies on different cases of community and places, to understand the dynamics of development negotiation between interested stakeholders, whether they are formal and/or informal parties.